Customary Institutions and Social Ecological Resilience in Forest and Water Governance: Kasepuhan Gelar Alam, Indonesia - Farell Firmansyah; Riska Tezara Go (CV. Komunitas Dunia Peternakan, 2026)
Customary communities govern forests and water through institutions embedded in everyday practice. This study examines how such institutions organize resource use and support social ecological resilience in Kasepuhan Gelar Alam, West Java, Indonesia. An exploratory qualitative case study involved semistructured interviews with 22 purposively selected participants, with interview sessions lasting approximately 40 to 60 minutes, alongside observation and field documentation. Thematic analysis examined customary authority, role distribution, forest zoning, water allocation, collective labour, knowledge of natural boundaries, and moral sanctions. Findings reveal an integrated governance system. Forest access is differentiated among hutan garapan (cultivation forest), hutan titipan (entrusted forest), and hutan tutupan (protected forest). Water for rice fields is organized through ulu-ulu or maningtim, conveyed through susukan, and maintained through gotong royong. Hukum cowal discourages monopolization, while kebendon, pamali, and kualat reinforce compliance through internalized moral responsibility. These arrangements connect forest protection, irrigation, rice production, reciprocity, and intergenerational obligations. Rather than demonstrating measured ecological outcomes, the study identifies institutional mechanisms through which the community regulates access, coordinates maintenance, and sustains continuity amid change. Customary governance can contribute to resilience when rules are locally legitimate, responsibilities are distributed, and resource use remains tied to reciprocal obligations. Policy engagement should recognize customary knowledge and authority without romanticizing or administratively simplifying living institutions.